Legend of Robber Kudeyar and Its Interpretation by N. Nekrasov in Poem “Who Lives Well in Russia” - O. V. Bogdanova; G. P. Talashov (Научный диалог, 2021)
The article considers the relevance of the interpretation and artistic embodiment of the legend “About two Great Sinners”, which is included in the chapter “A Feast for the whole World” of the poem by N. Nekrasov “Who lives well in Russia”. The authors emphasize that the Nekrasov episode, on the one hand, is based on a familiar folklore plot, on the other — it is interpreted by the poet differently than is traditionally accepted in folk texts. The analysis pointed out that, if in the folklore emphasis is placed on the image of the robber Kudeyar undergoing spiritual transformation, in the poem of Nekrasov focus redirected to the image of “the other robber”, pan Glukhovsky, who, in the view of the author of the poem, is the “most sinful of all”. The article pays special attention to the aspect of the displacement of moral components by social ones. It is demonstrated that Nekrasov approach to solving the core issue of the head, “Who in Russia most sinful of all?” biased and removed from under-standing the triad of “sin of the landowner, sin of the robber, sin of the peasant” pro-posed by the heroes of the Chapter “Feast...”, but makes a scene-meaning “substitute” all “sinners” episodes only responsible for the sinner recognizes the nobleman, only at the social level, opposed to the peasant.